2021
DOI: 10.1001/jamadermatol.2021.0596
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Topical Timolol for the Treatment of Infantile Hemangioma in the Early Proliferative Stage

Abstract: IMPORTANCETreatment of infantile hemangioma (IH) with topical timolol in the first 2 months of life (early proliferative phase) may prevent further growth and the need for treatment with oral propranolol. To our knowledge, no studies have determined whether beginning early treatment with timolol for IH is better than in other proliferative stages.OBJECTIVE To evaluate the efficacy and safety of timolol maleate solution, 0.5%, for the early treatment of IH in infants younger than 60 days.DESIGN, SETTING, AND PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…The 595‐nm PDL is the laser of choice for vascular malformations and residual capillary dilation. Due to the thermally induced lysis of collagen, it can promote the deposition of adipose tissue and correct anatomical aberrations, promote tissue remodeling, and is associated with the reduction of transforming growth factor‐B1 (TGF‐B1) 6 . Complications after PDL treatment can manifest as immediate purpura, erythema, edema, and blisters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 595‐nm PDL is the laser of choice for vascular malformations and residual capillary dilation. Due to the thermally induced lysis of collagen, it can promote the deposition of adipose tissue and correct anatomical aberrations, promote tissue remodeling, and is associated with the reduction of transforming growth factor‐B1 (TGF‐B1) 6 . Complications after PDL treatment can manifest as immediate purpura, erythema, edema, and blisters.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the number of laser treatments for six group seriously affect the mental health and quality of life of children and their families. 6 The current methods for treating IH include oral propranolol, topical timolol, oral glucocorticoids, laser treatment, surgical treatment, injection treatment, and freezing. In systemic treatment, propranolol is the first-line drug for the treatment of complex infant hemangioma.…”
Section: Comparison Of Adverse Reactionsmentioning
confidence: 99%
“…On the contrary, Ying et al showed in a prospective study that topical timolol had a worse visual effect than PDL laser treatment [50]. A recent randomized clinical trial confirmed the safety of 0.5% timolol maleate solution but showed no significant differences in IH resolution in comparison to placebo when administered in the early proliferative stage [51]. Topical timolol was also reported to be effective in the treatment of an iris hemangioma [52].…”
Section: Timololmentioning
confidence: 99%
“…Timolol maleate is a topical formulation of nonselective beta-blockade that has proven beneficial for the management of small, superficial IH 122–126. The most common treatment regimen uses 0.5% gel forming solution, 1 drop gently rubbed into the IH twice a day 54,127.…”
Section: Treatmentmentioning
confidence: 99%
“…89 Topical Beta-Blockade Timolol maleate is a topical formulation of nonselective beta-blockade that has proven beneficial for the management of small, superficial IH. [122][123][124][125][126] The most common treatment regimen uses 0.5% gel forming solution, 1 drop gently rubbed into the IH twice a day. 54,127 In a multicenter retrospective cohort study of 731 patients with IH treated with topical timolol, therapy duration and thickness ≤ 1 mm were significant predictors of positive treatment response.…”
Section: Treatmentmentioning
confidence: 99%